2016
DOI: 10.3390/antiox5040033
|View full text |Cite
|
Sign up to set email alerts
|

Tart Cherry Extracts Reduce Inflammatory and Oxidative Stress Signaling in Microglial Cells

Abstract: Tart cherries contain an array of polyphenols that can decrease inflammation and oxidative stress (OS), which contribute to cognitive declines seen in aging populations. Previous studies have shown that polyphenols from dark-colored fruits can reduce stress-mediated signaling in BV-2 mouse microglial cells, leading to decreases in nitric oxide (NO) production and inducible nitric oxide synthase (iNOS) expression. Thus, the present study sought to determine if tart cherries—which improved cognitive behavior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Moreover, data obtained for the glial and microglial markers showed a reduction of astrocyte size in the treated groups compared to DIO. This indicates a regression of the inflammatory process, as previously demonstrated [80], in particular with juice supplementation. Our results have also shown a significant regression of the macrophagic state of IBA-1-positive cells, especially in the CA1 subfield, where we found a reduction of the activated status of microglial cells in DS and DJS groups with respect to the obese group.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, data obtained for the glial and microglial markers showed a reduction of astrocyte size in the treated groups compared to DIO. This indicates a regression of the inflammatory process, as previously demonstrated [80], in particular with juice supplementation. Our results have also shown a significant regression of the macrophagic state of IBA-1-positive cells, especially in the CA1 subfield, where we found a reduction of the activated status of microglial cells in DS and DJS groups with respect to the obese group.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, platelet chemokines are produced following stimulation of TNF-α and IL-1β [68], which result in recruitment of leukocytes to the site of vascular injury and enhancement of inflammatory processes. Recently, some studies have revealed that anthocyanin supplementation significantly reduces the serum lipid [69] and pro-inflammatory cytokine levels [7072], consistent with the effects of anthocyanins observed in our previous studies [32, 35]. In the present study, we first revealed that the reductions in the platelet chemokine levels caused by anthocyanins were positively correlated with the changes in the inflammatory marker and blood lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…Cherries are one of the richest sources of anthocyanins and antioxidants-substances and are more effective than vitamin C and are four times more potent than vitamin E in antioxidant activity [ 37 ]. The anthocyanins in cherries give a dark red colour [ 38 ] and have been shown to be associated with the prevention of lifestyle-related diseases such as cancer, diabetes and cardiovascular diseases [ 39 ] and neurodegenerative disease [ 40 ]. Moreover, recently, Keane et al [ 41 ] demonstrated that the acute supplementation with tart cherry juice can lower blood pressure and improve some aspects of exercise performance, highlighting the beneficial impact of bioactive compound and physical activity.…”
Section: Introductionmentioning
confidence: 99%